How to map Islamic banking research globally? - Hendrieta Ferieka; Irmatul Hasanah (Journal of Enterprise and Development (JED), 2023)
Purpose — This study aims to get a visual picture of the development of Islamic banking research globally from time to time. The theme of “Islamic Banking” is interesting to discuss because the principles of Islamic banking are based on the balance between well-being and prosperity, based on equality, risk-sharing, and ethical conduct, which makes Islamic banks different from conventional banks.Method — The type of research used in this study is descriptive quantitative research, which is based on literature by taking data sourced from Dimensions.ai which will then be analyzed using quantitative methods based on bibliographies from journals/or articles, using the help of the R-Biblioshiny application.Result — Research documents with the topic and keyword of “Islamic bank” still increasing every year. But the growth and development are just in certain countries, especially “Southeast Asia” in Asia. Based on the bibliometric, “Hassan MK and Sufian F” are “the most productive writers”. The most productive affiliates are “Islamic Azad University” followed by “International Islamic University Malaysia”. However, the dominant citation of the article with this subject is from “Finland”, namely “Gronroos C”.Contribution — This study visualized the trends in the most popular keywords, journals, and authors of articles on the theme of Islamic Banking, which has been quite a popular theme in recent years, thereby providing information for researchers specializing in the field of Islamic banking and finance research. This theme has the potential to continue to be developed.